AUDIT COMMITTEE CHARACTERISTICS AND VOLUNTARY DISCLOSURE (STUDY ON MANUFACTURING COMPANIES IN 2017-2019) - Safitri Nurul Aisyah; Isna Putri Rahmawati (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2022)
This study centers on how the audit committee's characteristics impact voluntary disclosure. The composition of the audit committee is shown by its size, percentage of independent commissioners, and gender diversity. This study used 255 observations over 3 years, from 2017 to 2019, and samples from industrial firms recorded on the Indonesia Stock Exchange. In this study, a multiple linear analysis is conducted. The results show that the audit committee size has a negative effect on voluntary disclosure. The ratio of independent commissioners and the gender diversity of the audit committee have a positive impact on voluntary disclosure.